Risk Factors of Mortality in Patients Hospitalized With Chronic Duodenal Ulcers. Issue 4 (April 2022) - Lin, Nicole; Smiley, Abbas; Goud, Manoj; Lin, Cynthia; Latifi, Rifat
Background: We aimed to identify risk factors of mortality in patients hospitalized with duodenal ulcers (DUs). Methods: A National Inpatient Sample–based retrospective cohort study from 2005 to 2014 was conducted on patients undergoing emergency admission for chronic DUs. Demographics, clinical data, and outcomes were collected. Multivariable logistic regression model was applied to find the risk factors of mortality. Results: 70 641 patients were included in this study, of which 30 525 (43%) were non-elderly (< 65 years) and 40 116 (57%) were elderly (65+ years) patients. 72% of non-elderly and 57% of elderly patients were males. Mortality rate of men vs women was similar in non-elderly group (1.9% vs 2%, respectively), whereas it significantly differed in elderly patients (4.5% vs 5.3%, respectively, P<.0001). Time to operation was 1.15 (1.83) days in survived vs 1.55 (3.86) days in deceased non-elderly patients ( P < .001). Time to operation was .85 (1.73) days in survived vs 1.79 (7.28) days in deceased elderly patients ( P < .001). In patients with operation, age, delayed operation, frailty, and presence of perforation were the main risk factors of mortality in both elderly and non-elderly patients. Invasive diagnostic procedure was shown as a protective factor in elderly patients. In the final model for patients with no operation, age, hospital length of stay, and frailty were the main risk factors of mortality in both elderly and non-elderly patients. Invasive diagnostic procedure was revealed as a protective factor in all patients as well. Conclusion: Early operation in patients with DU requiring surgical intervention is essential to improve the outcomes.